2020
DOI: 10.3389/fpls.2020.00196
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light on Plastid Differentiation, Chlorophyll Biosynthesis, and Essential Oil Composition in Rosemary (Rosmarinus officinalis) Leaves and Cotyledons

Abstract: It is unclear whether light affects the structure and activity of exogenous secretory tissues like glandular hairs. Therefore, transmission electron microscopy was first used to study plastid differentiation in glandular hairs and leaves of light-grown rosemary (Rosmarinus officinalis "Arp") plants kept for 2 weeks under ambient light conditions. During our detailed analyses, among others, we found leucoplasts with tubuloreticular membrane structures resembling prolamellar bodies in stalk cell plastids of pelt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Some researchers have suggested the similarity of electron-dense materials inside plastids to ferritin protein clusters (Voith von Voithenberg et al 2019 ). Electron-dense inclusions were also detected in the mesophyll of Rosmarinus officinalis during etio-chloroplast differentiation (Böszörményi et al 2020 ). Altogether, the electron-dense inclusions in chloroplasts within PT and OC might indicate that the chloroplast development is still in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested the similarity of electron-dense materials inside plastids to ferritin protein clusters (Voith von Voithenberg et al 2019 ). Electron-dense inclusions were also detected in the mesophyll of Rosmarinus officinalis during etio-chloroplast differentiation (Böszörményi et al 2020 ). Altogether, the electron-dense inclusions in chloroplasts within PT and OC might indicate that the chloroplast development is still in progress.…”
Section: Discussionmentioning
confidence: 99%
“…In the former, cubic membrane formation was induced by starvation and/or autophagy processes of the amoeba cells, during which they were slowing the degradation of the organelle and thus contributed to the survival of the cell upon stress conditions (Chong et al, 2017 ). In case of plastids, they occurred either in etioplasts or etio-chloroplasts in the form of PLBs and were thus strongly associated with intensive Chl biosynthesis and accumulation of LPOR ( Figure 5 ) (Solymosi and Schoefs, 2008 , 2010 ; Solymosi and Aronsson, 2013 ) or in secretory plastids having active isoprenoid biosynthesis involving the plastid located MEP-pathway or biosynthesis of hydrophobic molecules such as cutin or suberin (Solymosi and Schoefs, 2010 ; Böszörményi et al, 2020 ). Rarely, such tubuloreticular membrane organizations could be interpreted as vesicle clusters (Lindquist et al, 2016 ) or as structures that appeared under various stress conditions [e.g., UV irradiation (Kovács and Keresztes, 2002 )].…”
Section: Lpor—an Enzyme Operating In Lipid Environmentmentioning
confidence: 99%
“…Secretory plastids containing tubuloreticular membranes were observed in various taxa and secretory tissues including extrafloral nectaries of Passiflora (Schnepf, 1961 ), plastids of various glandular hairs [e.g., Cannabis (Hammond and Mahlberg, 1978 ; Kim and Mahlberg, 1997 ; Solymosi and Köfalvi, 2017 ), Artemisia (Ascensao and Pais, 1982 ), Chrysanthemum (Vermeer and Peterson, 1979 ), Centrolobium (Matos and Paiva, 2012 ), Platanthera (Stpiczyńska et al, 2005 )], Mentha piperita (Amelunxen, 1965 ; Turner et al, 2000 , 2012 ), Perilla ocymoides (Kashina and Danilova, 1993 ) and Rosmarinus officinalis (Böszörményi et al, 2020 ). Some authors suggested that light may play a role in the formation of these peculiar membrane structures in secretory cells (Kashina and Danilova, 1993 ), while others observed identical structures in the neck cells of the peltate glandular hairs of both light-grown and dark-forced shoots (Böszörményi et al, 2020 ). Detailed comparative analyses about these peculiar non-bilayer membranes of Rosmarinus officinalis plastids have clearly demonstrated important structural differences.…”
Section: Lpor—an Enzyme Operating In Lipid Environmentmentioning
confidence: 99%
See 2 more Smart Citations